Prognostic relevance of melanoma antigen D1 expression in colorectal carcinoma - Zeng, Zhao-lei (BioMed Central, 2012)
BACKGROUND: Melanoma antigen D1 (MAGED1) is a member of the type II melanoma antigen (MAGE) family. The down-regulation of MAGED1 expression has been shown in breast carcinoma cell lines and in glioma stem cells and may play an important role in apoptosis and anti-tumorigenesis. However, there is no report on its clinical role in colorectal cancer (CRC). METHODS: We examined the expression of MAGED1 by qPCR in colorectal cancer tissues and their adjacent non-tumorous tissues taken from 6 cases and performed Western blotting and IHC analyses. In addition, we analyzed MAGED1 expression in 285 clinicopathologically characterized colorectal cancer patients. RESULTS: MAGED1 expression was significantly down-regulated in colorectal cancer tissues compared with adjacent non-tumorous tissues and was associated with clinical stage (p < 0.001), T classification (p = 0.001), N classification (p < 0.001), M classification (p < 0.001) and pathologic differentiation (p = 0.002). Patients with lower MAGED1 expression had a shorter survival time than those with higher MAGED1 expression. Univariate and multivariate analyses indicated that MAGED1 expression was an independent prognostic factors (p < 0.001). CONCLUSIONS: MAGED1 may serve as a novel prognostic biomarker of human colorectal cancer.